The challenge of integrating the healthcare enterprise. - Grimes, S.L (IEEE Engineering in medicine and biology magazine)
Clinical engineers face technical challenges and opportunities in healthcare technology as results of changing focus in healthcare and the computerization and interconnection of medical devices and systems. Combined, these trends will increasingly move us away from the traditional "bricks and mortar" hospitals and physician's offices and move us toward their virtual successors. Ultimately, diagnosis and treatment will take place at an earlier stage. A major challenge to achieving this goal has been the diversity of current healthcare technologies and the paucity of technical standards for exchanging useful information between different medical devices. The consequence is a technical "Tower of Babel", where these disparate devices lack a common means of communication. The answer to this challenge is an initiative known as Integrating the Healthcare Enterprise (IHE). IHE brought together healthcare information and medical imaging systems industry members "to agree upon, document, and demonstrate standards-based methods of sharing information in support of optimal patient care". By developing integration profiles that detail core processes such as scheduled workflow, image presentation, information access, record retrieval, reporting, and charge posting and adopting existing standards. IHE defines guidelines that medical device manufacturers can follow to ensure their device will interface and effectively communicate with a device from another manufacturer. IHE holds promise to transform the existing technical "Tower of Babel" into sets of integration profiles that will facilitate interoperability of medical devices. The success of IHE will lead to technological integration and thereby meet one of the most critical challenges as healthcare systems move to the next level.